Brillouin optical correlation domain analysis with more than 1 million effective sensing points based on differential measurement - Kim, Yong Hyun; Lee, Kwanil; Song, Kwang Yong (OPTICAL SOC AMER, 2015)
Large increase of effective sensing points in Brillouin optical correlation domain analysis (BOCDA) is achieved by simultaneously applying double modulation and optical time gate based on differential measurement scheme. The noise substructure of Brillouin gain spectrum induced by the double modulation is effectively suppressed by the differential measurement, leading to 2,000 times enlargement of the measurement range. Distributed strain and temperature sensing along a 10.5 km fiber with spatial resolution of less than 1 cm is experimentally demonstrated which corresponds to over 1 million effective sensing points. (C) 2015 Optical Society of America
Keywords: DISTRIBUTED STRAIN-MEASUREMENT; ORDER SPATIAL-RESOLUTION; MEASUREMENT SCHEME; SENSOR; MODULATION; SCATTERING; AMPLIFICATION; PROPOSAL